The Colonial Advice Social-Epistemic Reflections on Coloniality and Biblical Scholarship - Klein Cardoso, Silas (2025)
Despite significant contributions on the topic, remnants of colonialist and imperialist ideas continue to be materially, conceptually, methodologically, institutionally, and pedagogically present in biblical scholarship. The situation comes at a great cost to the so-called “minority” scholars, whose challenges lie beyond the production of good and reliable biblical scholarship. This article reflects on the social-epistemic challenges faced by these scholars and questions the helpfulness of this terminology. From an anthology of colonialist “advices” received by the author in the last five years, and using insights from the sociology of knowledge and decolonial thinking, the article reflects on the coloniality of biblical studies. Therefore, in conversation with Latin American critical thinking and under what Freire called “raiva justa” (righteous wrath), five pillars of injustice are unveiled from the pieces of advice, and suggestions for radical action are provided to inform new contributions to biblical theology.
Keywords: Latin American thinking; sociology of knowledge; decolonial biblical scholarship; colonial biblical scholarship